Inclusion as a co-produced accomplishment: a stakeholder-sensitive systematic review of barriers and facilitators in inclusive physical education - Aidil Syaputra; Jeki Haryanto (Global Econedu, 2026)
Inclusive physical education (IPE) is considered by many to be the best way to allow people with disabilities, equal opportunities for engaging in physical activities but its actual implementation varies greatly within educational systems. This systematic review was conducted to uncover the barriers and facilitators to IPE implementation and to see how various stakeholders influence the process. The study was carried out in line with the PRISMA (2020) guidelines. Through a structured search of the Scopus database, 357 articles were found; after excluding 14 duplicates and through successive screening, 18 studies published between 2021 and 2025 were selected according to the inclusion and exclusion criteria. Barriers and facilitators were synthesised using a socio-ecological framework distinguishing individual, relational, and structural determinants. The corpus (n = 18) was predominantly qualitative and spanned twelve countries, integrating the perspectives of teachers, pre-service teachers, and students with disabilities. Across the included studies, inadequate teacher preparation was the most consistently reported barrier, while practicum-based teacher education emerged as the most strongly evidenced facilitator. Notably, multiple studies converged on the finding that physical placement in mainstream classes did not, by itself, secure social belonging. Thematic analysis unfolded that lack of sufficient initial and continuous teacher training, poor structural settings, and inflexible pedagogical conventions are still major obstacles, whereas focused teacher education, reflective and individualized teaching methods, and nurturing school environment act as facilitators. Results show that physical inclusion alone is not sufficient to bring about social inclusion. This review offers an integrated, stakeholder-aware narrative on IPE implementation, provides useful advice for teacher training, and lays down a research agenda emphasizing student voice and longitudinal designs.